Work Discipline and Organizational Commitment as Drivers of Employee Performance in Indonesian Credit Union Cooperatives: The Mediating Role of Job Satisfaction (Literati Global Network, 2026)
Purpose: This study examines the direct and indirect effects of work discipline and organizational commitment on employee performance through job satisfaction as a mediating variable, addressing critical human resource management challenges in Indonesian cooperative financial institutions serving rural and low-income communities in Eastern Indonesia. Method/approach: A quantitative cross-sectional survey collected data from 30 employees at KSP Kopdit Pintu Air Branch Kefamenanu, North Central Timor Regency, East Nusa Tenggara Province, during March 2025. Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.9 analyzed both direct relationships and mediating pathways, with rigorous measurement validation and bootstrapping procedures (5,000 resamples) for indirect effects testing following contemporary mediation analysis standards. Findings: Work discipline significantly predicts employee performance (β = 0.526, t = 5.154, p < 0.001) and job satisfaction (β = 0.121, t = 2.086, p = 0.037). Organizational commitment demonstrates stronger direct effects on performance (β = 0.587, t = 6.463, p < 0.001) and satisfaction (β = 0.089, t = 2.087, p = 0.037). Job satisfaction strongly influences performance (β = 0.624, t = 6.162, p < 0.001) and partially mediates both discipline-performance (β = 0.076, 95% CI [0.008, 0.158], p = 0.033) and commitment-performance relationships (β = 0.056, 95% CI [0.006, 0.125], p = 0.033). Combined predictors explain 68.1% of performance variance (R² = 0.681). Limitations: Small sample size (N = 30) from single branch limits statistical power, generalizability, and ability to detect small effects. Cross-sectional design precludes causal inference and temporal precedence establishment. Self-report measures introduce potential common method bias despite procedural remedies. Future research should employ larger multi-branch samples (N > 200), longitudinal designs with >3 measurement waves, and objective performance indicators complementing self-reports. Implications: Cooperative managers should implement integrated human resource strategies encompassing (1) disciplinary systems balancing accountability with supportive enforcement, (2) commitment-building programs emphasizing organizational values and community welfare missions, and (3) satisfaction enhancement through fair compensation, career development, and supportive climates recognizing satisfaction as critical psychological mechanism translating behavioral and motivational inputs into performance outcomes. Contribution: This study extends Social Exchange Theory and Affective Events Theory to under-investigated cooperative financial sector in rural Indonesia, validates mediation mechanisms in non-Western values-driven organizational contexts, advances methodological rigor through contemporary PLS-SEM bootstrapping techniques, and provides strategic guidance for Indonesia’s 123,048 cooperatives serving marginalized communities.